Avaliação do desempenho e da influência das condições ambientais e operacionais de lagoas de estabilização, com base em um banco de dados internacionais - Maria Fernanda Espinosa Cordero (2016)
This research consists of an evaluation of the performance of full-scale waste stabilization ponds, using the effluent concentrations and removal efficiencies for BOD, total suspended solids (TSS), ammonia nitrogen (N-Ammonia), thermotolerant coliforms (TTC) and E. coli. Compliance with different water quality goals for the final effluent concentrations and overall removal efficiencies were also assessed for the five parameters mentioned above. More than 55,000 data were evaluated from 388 waste stabilization pond systems situated in different locations and regions of North America (Missouri and Georgia) and South America (Brazil, Ecuador and Bolivia). The systems comprised the following seven configurations: facultative ponds (FP); facultative and maturation ponds (FP + MP); anaerobic and facultative ponds (ANP+FP); aerated and facultative ponds and/or maturation ponds (AEP+FP/MP); anaerobic reactors and facultative ponds (AR+FP); anaerobic reactor and other treatment unit (facultative pond or anaerobic filter) and maturation pond (AR+OT+MP); and ponds with post treatment (P+PT). The lack of influent concentration data for N-Ammonia and E. coli was a limitation for the evaluation of the removal efficiencies for these parameters. The results for BOD and TSS influent concentrations classified the wastewater as strong domestic sewage. The average influent concentration of BOD (415 mg/L) was greater than 300 mg/L, a value normally used for design projects. The concentrations of E. coli and thermotolerant coliforms demonstrated that the effluent can be used for restricted Type H (subsurface irrigation), as defined by the WHO Guidelines. The results showed significant differences between the performance of configurations with respect to the BOD, TSS, TTC and E. coli removal efficiencies. The ANP+FP and AR+OT+MP configurations had the best performance for the removal of BOD; the AR+FP configuration performed best for the removal of TSS and TTC; the FP+MP and FP configurations provided the best removal of E. coli. There were no significant differences between removal efficiencies for N-Ammonia with the different configurations. More than 90% of the data had very low compliance with water quality goals. There were no significant correlations between the performance and the operational factors (hydraulic retention time, organic rate and overload index) and the environmental factors (temperature and insolation). In most cases of the study, showing that these the operational and environmental factors alone cannot explain the performance of the ponds. This demonstrated that the performance of these systems likely results from a multitude of interacting factors simultaneously.